FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR SEKTOR SEMEN - maharani, destin alfianika; Fatimah, Ika Siti; Anjani, Lulu Alfiatun; Kurniati, Rani alfianika (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2022)
This study aims to determine the factors that can affect the profitability of the company. The sampling technique in this research is using purposive sampling. Meanwhile, the data collection method used in this research is documentation and literature study. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that the current ratio, debt ratio, firm size and total asset turnover have no effect on profitability, while sales growth has an effect on profitability.